Identification of a new HLA‐A*24 allele, A*24:309, in an Italian bone marrow donor. (21st December 2015) - Sciarrino, R.; Putignano, A. L.; Biagini, C.; Rombolà, G.; Curcio, M.
Abstract : A novel class I human leukocyte antigen allele HLA‐A*24:309 is described.